Multiphase SVPWM Strategy Analysis and Implementation of Seven-Phase Permanent Magnet Synchronous Motor. (21st October 2020) - Lu, Mingli; Zhang, Dong; Xu, Benlian; Yang, Haodong; Xin, Yi
Abstract : The multiphase motor drive systems have become a focus in many application areas such as ship electric propulsion, urban mass transit, aerospace, and weapon equipment, as they are characterized by high power density, low torque pulsation as small torque ripple, large output power, strong fault tolerance, and high reliability. However, with the increase of the phase number of the motor, the current harmonic component increases correspondingly, which leads to the decrease of the control performance compared with the three-phase system. In order to overcome this challenge, implementation method of driving control technology for seven-phase permanent magnet synchronous motor (PMSM) based on SVPWM algorithm is discussed thoroughly in this paper. Simulink and experiments have been developed to check its practical feasibility. The results show that the near-six vector SVPWM algorithm (NSV-SVPWM) achieves better performance than other methods.